Plant-based diet - influence on general health - Pietrusińska, Patrycja; Dziewierz, Anna; Sobiński, Adam; Miśkewicz, Joanna; Dudek, Aleksandra; Sadowska, Aleksandra; Moder, Jakub; Welkier, Aleksandra; Kwaśniewska, Paula; Śliwa-Tytko, Patrycja (Quality in Sport, 2025)
Introduction An increasing number of individuals worldwide are adopting a plant-based diet, which has been highlighted for its health benefits in various scientific studies. Nevertheless, research indicates that an improperly balanced plant-based diet, excluding animal products, may lead to nutrient deficiencies and disrupt the proper functioning of various bodily systems through multiple pathways Aim The aim of this review is to consolidate and summarize the existing research and literature regarding the effects of a plant-based diet on general health. Review methods The review was based on publicly available PubMed and Google Schola databases using the following phrases: plant-based diet, vegan diet, vegetarianism. Conclusion: When properly planned and supported by appropriate supplementation, a plant-based diet can positively influence both female and male reproductive health, improve sleep quality, enhance overall well-being, aid in weight management, and contribute to the prevention of diabetes and cardiovascular diseases. However, as the number of dietary exclusions increases, so does the risk of deficiencies in essential vitamins and minerals. Inadequate levels of these nutrients may lead to physiological abnormalities and adverse health outcomes, underscoring the critical importance of balanced dietary planning and monitoring.